2003
DOI: 10.1063/1.1568162
|View full text |Cite
|
Sign up to set email alerts
|

1.3 μm wavelength vertical cavity surface emitting laser fabricated by orientation-mismatched wafer bonding: A prospect for polarization control

Abstract: We propose and demonstrate a long-wavelength vertical cavity surface emitting laser (VCSEL) which consists of a (311)B InP-based active region and (100) GaAs-based distributed Bragg reflectors (DBRs), with an aim to control the in-plane polarization of output power. Crystal growth on (311)B InP substrates was performed under low-migration conditions to achieve good crystalline quality. The VCSEL was fabricated by wafer bonding, which enables us to combine different materials regardless of their lattice and ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
(15 reference statements)
1
15
0
1
Order By: Relevance
“…For example VCSELs based on noncylindrical cavities, on spatial gain or loss anisotropy, on the use of external stress or optical feedback have been successfully realized. 5,[9][10][11] They show a polarization control toward a specific direction, with an orthogonal polarization suppression ratio ͑OPSR͒ being for the best value close to 30 dB. Nevertheless, most of these realizations increase the fabrication complexity and cost.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…For example VCSELs based on noncylindrical cavities, on spatial gain or loss anisotropy, on the use of external stress or optical feedback have been successfully realized. 5,[9][10][11] They show a polarization control toward a specific direction, with an orthogonal polarization suppression ratio ͑OPSR͒ being for the best value close to 30 dB. Nevertheless, most of these realizations increase the fabrication complexity and cost.…”
mentioning
confidence: 96%
“…As already reported, we experimentally observed that the QW VCSEL dominant polarization switches on the sample, the extracted OPSR varying from 26 dB down to Ϫ14 dB, in a very dispersive way. [5][6][7][8][9] In opposite, Fig. 3͑b͒ represents the measurements for the QDH VCSELs.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This technology is widely used for manufacturing complex optoelectronic and microelectronic devices [2][3][4]. Direct wafer bonding of III-V/Si requires two smooth, clean surfaces to be brought into contact at room temperature and then annealed at a high temperature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be preferable to utilize an active region based on anisotropic polarization gain to solve the problem of the polarization. VCSEL based on strained quantum-wells (QWs) grown on (311)A or (311)B oriented substrate evidences a strong polarized laser emission [6,7]. Another solution to get an active region with gain anisotropy without using a special substrate may be the QWires growth on InP(100).…”
Section: Introductionmentioning
confidence: 99%